Mobility and verbal communication patients undergoing awake craniotomy - Ioannis Sapountzis; Sofia Anevlavi; Vasiliki Nterou; Maria Dantsiou; Nikolaos Georgakoulias; Giannoula Ntavoni (Ene, 2017)
Introduction: The surgical treatment of gliomas in traffic areas, speech is aimed at the maximum ablation, with minimal postoperative neurological deficit. The election procedure is craniectomy with the patient conscious (awake craniotomy). The conscious craniotomy with intraoperative mapping of the cerebral cortex, superior to conventional craniotomy microsurgery in resection rates during hospitalization and recovery time of the operated patients with lesions in speech and movement area. Purpose: The aim of the research was to study cases with brain gliomas in rolandeio area and literary centers, the investigation and study of preoperative neurological status and imaging findings of patients and end their correlation with the postoperative course and outcome of patients. Methods: This is a study population of 43 patients of Neurosurgery Clinic of General Hospital «G. Gennimatas» with gliomas in the movement and speech area treated surgically within four years. Statistical analysis was done using the SPSS15. Preoperative and postoperative classification based on the examination of muscle strength and speech became into four groups: I - without focal motor, II - mild motor, III - moderate kinetic, IV - heavy motor deficit and finally two groups regarding disorders word: a- undisturbed and B with speech disorders . Macroscopically complete removal of over 95%, defined as the absence hearth space-occupying lesion in the postoperative CT scan . Results: The age of patients ranged from 26-69 years with a mean of 43.7 years. Among patients who underwent craniectomy, complete removal was achieved in 36 patients (83.75%) and partly in 7 patients (16.3%). Postoperatively 6 patients (18.6%) showed improvement of motor deficit, 23 patients (53.49%) experienced unchanging muscle strength, 12 patients (27.91%) showed a kinetic deterioration in 9 patients (20.93%) first observed - emfanizomenes speech disorders, referred to as complications. Conclusions: The craniotomy on the patient alert is a reliable method of ensuring the total ablation volume in traffic areas, while speech integrity of neurological patients. This is a special and critical intraoperative procedure because of the particular communication and cooperation both between the surgical team, and between the surgical team and the patient.